Challenges and solutions in maintaining student academic integrity in the era of artificial intelligence - Christian Wiradendi Wolor; Faerozh Madli; Mahmoud Ali Rababah; Wong Chee Hoo (Library Progress International, 2024)
In recent years, international research in the field of academic integrity has turned to examine issues specifically in the use of artificial intelligence. This research aims to provide a holistic approach in dealing with violations of academic integrity among students amidst the spread of artificial intelligence practices with a systematic literature review approach. The results of this research show that there are five approaches that can be used to maintain academic integrity amidst the increasing use of artificial intelligence. Ultimately, an integrity solution that combines prevention and enforcement approaches to address future academic integrity issues.